Seroprevalence of Q-fever, spotted fever, typhus group Rickettsia and Orientia among febrile patients visiting hospital-based sentinel sites in Uganda - Eneku, Wilfred; Erima, Bernard; Byaruhanga, Anatoli Maranda; Nora, Gillian Cleary; Atim, Gladys; Tugume, Titus; Ukuli, Qouilazoni Aquino; Kibuuka, Hannah; Mworozi, Edison; Christina, Douglas; Jeffrey, William Koehler; Michael, Emery von Fricken; et al. (PAMJ - One Health, 2023)
Introduction: rickettsioses are emerging zoonotic febrile illnesses transmitted to humans by ticks, fleas, lice, and mites. Q-fever, Spotted fever group (SFG), Typhus group (TG) rickettsia and Scrub typhus (STG) have been reported with varying prevalence across East Africa. However, little is known about the burden of exposure in Uganda. The aim of this study was to determine the seroprevalence and associated risk factors of rickettsial diseases in Uganda. Methods: a total of 460 archived serum samples collected from patients with fever of unknown origin after screening across five hospital-based sentinel sites were analysed. The samples were collected during 18-month period of active surveillance for acute febrile illnesses, from January 2018 through June 2019. We performed IgM ELISA tests on the 460 sera for SFG and TG rickettsia, IgM IFA for STG and Phase 2 IgG ELISA for Q-fever. We also assessed risk factors associated with the serostatus. Results: the population comprised predominantly children, had balanced gender proportions, with 66% coming from rural areas. The overall seroprevalence of SFG rickettsiosis was 6.3%; however, 11.5% and 10.8% prevalence rates were observed in Gulu and Bwera hospitals respectively. This was higher than the 3.7% observed in the capital city Kampala, although the differences were not statistically significant (Fisher's exact = 0.489). Overall seropositivity of Q-fever was 7.6%, although Bwera Hospital had the highest rate (12.5%) and Mulago had the lowest rate (2%). The differences were not considered statistically significant (Fishers exact= 0.075). Increasing age (OR-adjusted=1.4, 95%CI=1.0-1.9, p=0.026) and rural background (OR-adjusted=2.6, 95%CI=1.6- 6.4, p=0.037) were both significantly associated with seropositivity for Q-fever, while only increasing age had higher odds for seropositivity for SFG rickettsia (OR-adjusted= 1.9, 95% CI= 1.4- 2.6, p<0.001). One serum sample of a 10-monthold male from Bwera hospital was reactive to both SFG and Q-fever antibodies. We found four sera reactive cases to typhus group IgM and another four reactive to Orientia spp. IgM. However, we were not able to determine associating factors due to low seropositivity rates. Conclusion: here, we report for the first time the seroprevalence of Qfever, SFG and STG in febrile patients in Uganda. This report also provides the second study in over five decades since the earliest report of TG rickettsia. Testing for these pathogens in patients with acute febrile illness with unknown etiology may hold value, however more studies are required to provide information on disease ecology, risk factors, and transmission dynamics of these pathogens in Uganda.
: a cross-sectional study